The First Meat Sector IPO: Al Shaheer Corporation. (September 2017) - Seyyed, Fazal Jawad; Butt, Arslan Shahid; Ashfaq, Hafsa
This case examines the June 2015 decision of Muhammad Asad, a fund manager at Al Meezan Investment Management Limited, to participate in the Initial Public Offering (IPO) of Al Shaheer Corporation, a leading meat sector company of Pakistan. He was interested in increasing the exposure of the Meezan Islamic Fund (MIF) to the food sector, provided attractive risk-adjusted returns could be achieved. Based on the research team analysis and his own assessment, Asad had to decide whether or not to participate in the IPO book building process and the number of shares to bid for at each price level. Both Market Multiples and Discounted Cash Flow (DCF) valuation methods had yielded share value higher than the IPO floor price of PKR 43 per share which encouraged Asad to consider the investment opportunity. He also had to decide on the amount that he could allocate to the IPO on behalf of MIF. Asad had to prepare his recommendations on the IPO for presentation and approval by the investment committee in the upcoming meeting. He has asked you to conduct an independent analysis and valuation of Al Shaheer stock over the weekend and share your findings with him early Monday morning.